2023
DOI: 10.3390/s23198146
|View full text |Cite
|
Sign up to set email alerts
|

Surface Subsidence Monitoring of Mining Areas in Hunan Province Based on Sentinel-1A and DS-InSAR

Liya Zhang,
Pengfei Gao,
Zhengzheng Gan
et al.

Abstract: Monitoring the surface subsidence in mining areas is conducive to the prevention and control of geological disasters, and the prediction and early warning of accidents. Hunan Province is located in South China. The mineral resource reserves are abundant; however, large and medium-sized mines account for a low proportion of the total, and the concentration of mineral resource distribution is low, meaning that traditional mining monitoring struggles to meet the needs of large-scale monitoring of mining areas in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…Consequently, it has gained extensive utilization in the field of surface subsidence monitoring [18][19][20][21][22]. Liya Zhang et al [23][24][25] employed Differential Interferometric Synthetic Aperture Radar (D-InSAR) technology to monitor surface subsidence in mining areas and investigated the spatiotemporal dynamic characteristics of subsidence. They concluded that underground mining aligns with the directional surface deformation and exerts a persistent and continuous impact on surface deformation.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, it has gained extensive utilization in the field of surface subsidence monitoring [18][19][20][21][22]. Liya Zhang et al [23][24][25] employed Differential Interferometric Synthetic Aperture Radar (D-InSAR) technology to monitor surface subsidence in mining areas and investigated the spatiotemporal dynamic characteristics of subsidence. They concluded that underground mining aligns with the directional surface deformation and exerts a persistent and continuous impact on surface deformation.…”
Section: Introductionmentioning
confidence: 99%